PELAKSANAAN SISTEM PENGADAAN BARANG BERBASIS E-PURCHASING DI PT. GLOBAL GEMILANG NUSA PERTIWI - Bagas Chandra Nur Adi Sulistyo; Nanik Sutarni; Burham Pranawa (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2025)
Presidential Regulation Number 12 of 2021 is an amendment to Presidential Regulation Number 16 of 2018 regarding the procurement of government goods and services. One of the key changes is the reinforcement of the e-purchasing system through electronic catalogs and online stores. This study aims to examine the implementation and effectiveness of this regulation in the context of e-purchasing carried out by suppliers, using PT. Global Gemilang Nusa Pertiwi as a case study. The research method used is empirical juridical, combining normative analysis of laws and regulations with empirical field data obtained through interviews and observation. The findings indicate that although the regulation normatively aims to achieve more transparent, efficient, and accountable procurement, its implementation still encounters several technical and administrative obstacles. These include lengthy product curation processes, technical issues within the e-catalog system, and limited digital literacy among regional suppliers. Thus, there is a need for strengthening technical capacities, improving digital infrastructure, and simplifying the curation process to ensure that e-purchasing implementation aligns with the spirit of bureaucratic reform and good governance.